Enzyme-Treated Soybean Meal Replacing Extruded Full-Fat Soybean Affects Nitrogen Digestibility, Cecal Fermentation Characteristics and Bacterial Community of Newly Weaned Piglets - Li, Hao; Yin, Jie; He, Xi; Li, Zhiqing; Tan, Bie; Jiang, Qian; Chen, Jiashun; Ma, Xiaokang (Frontiers in Veterinary Science, 2021)
The study investigated the impact of soybean protein from different processing on the performance, dietary nitrogen digestibility, cecal fermentation characteristics and bacterial community in newly weaned piglets. The piglets were allocated to two dietary treatment and fed with the extruded full-fat soybean diet (EFS group) and enzyme-treated soybean meal diet (ESBM group), respectively. The piglets in ESBM group showed greater nitrogen digestibility and feed efficiency, and lower diarrhea rate in comparison to piglets in EFS group (P < 0.05). Cecal samples from piglets in ESBM group contained greater concentration of acetate, propionate and total SCFAs (P < 0.05), and lower contents of isobutyrate, isovalerate, total BCFAs, NH3-N and putrescine (P < 0.05) than cecal samples from piglets in the EFS group. The cecal samples from piglets in ESBM group contained greater abundances of g_Blautia, g_Coprococcus_3, g_Fusicatenibacter, and g_Bifidobacterium than the cecal sample from piglets in the EFS group, which could promote to protect intestinal health. In summary, enzyme-treated soybean meal may enhance the growth performance of weaned piglets via increasing the dietary nitrogen digestibility, preventing protein fermentation in the hindgut, which shed light on the mechanism of dietary protein in improving gut health.